STUDYING ON THE SOLFEGGIO TEACHING METHOD FOR FIRST YEAR STUDENTS IN GANNAN NORMAL UNIVERSITY COLLEGE OF MUSIC, JIANGXI PROVINCE - Jiadong, Xu; Banchongsilpa, Orawan (Asia Pacific Journal of Religions and Cultures, 2025)
Research purpose is to study the teaching method of solfeggio for the first-year students in College of Music, Gannan Normal University, Jiangxi Province. The research method was the qualitative research and the sampling was the first-year students in Gannan Normal University. The research tools were: interview form, observation form, and verification form. The results of the study were (1) Solfeggio teaching method is a comprehensive training process, which involves reading notation, singing the scale, the vocalization, singing accurately (rhythm, melody, intonation, tonality, expression) and ear training. Through the training in these aspects, learners can comprehensively improve their music literacy and performance ability, and better understand and interpret music works, (2) Solfeggio teaching method is an important part of music education, aiming at cultivating students’ music perception ability, rhythm sense, intonation sense and expression ability. In order to comprehensively evaluate and optimize the teaching effect of solfeggio teaching method, the observation form of solfeggio teaching method from six aspects: teaching objectives, teaching contents, teaching methods, teaching tools, professional quality of teachers and student participation. (3) The IOC result of the interview form is 0.901 higher than 0.6. It is permitted for research purpose. (4) The IOC result of the observation form is 0.89 higher than 0.6. It is permitted for research purpose.